ANALISIS TINGKAT KEBANGKRUTAN PT SRI REJEKI ISMAN TBK MENGGUNAKAN MODEL ALTMAN Z-SCORE (2019-2023) - Sari, Wulan; Salsa Karwati; Nurhana Dhea Parlina (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This study analyzes the bankruptcy risk of PT Sri Rejeki Isman Tbk (SRIL) from 2019 to 2023 using the Altman Z-Score model. This model is applied to evaluate five key indicators: Working Capital to Total Assets, Retained Earnings to Total Assets, EBIT to Total Assets, Market Value of Equity to Book Value of Liabilities, and Sales to Total Assets. The results indicate significant financial fluctuations, with a tendency to remain in the grey area and distress categories. The average Z-Score of 1.53 suggests that the company's financial condition is still far from the safe category (>2.99). The most critical condition occurred in 2021 when the Z-Score dropped drastically to -0.70 due to high debt burdens, declining operating profits, and the loss of market equity value. Although there was an improvement in 2022 and 2023, the company still faces major challenges in enhancing profitability and managing financial risks effectively. Theoretically, this study confirms the relevance of the Z-Score model in assessing a company’s financial health and predicting potential bankruptcy. These findings reinforce the importance of Z-Score analysis as a predictive tool in anticipating financial risks, especially for companies with high debt levels. Practically, PT Sritex needs to implement a more conservative financial management strategy, including debt reduction and operational efficiency improvements, to avoid future financial distress.